The Influence of Company Size, Audit Opinion, and Operating Profit on Audit Report Lag - Tulfitri, Aisya; Lilianti, Emma; Mursalin (Jurnal Ilmiah Wahana Akuntansi, 2021)
Abstract This observasion activity intends to determine the impact of several background aspects such as company size, audit opinion, operating profit which has a direct influence on audit report lag. The population chosen by the researcher is to take advantage of all of the property and real estate companies that have joined the IDX, in the 2017-2019 period, consisting of 61 companies. Sampling is with purposive sampling method, a final sample of 20 companies. Then perform an analysis data that utilizes multiple linear regression using the SPSS program. So the results obtained in this study conclude that company size and audit opinion basically do not affect audit report lag. However, it was found the effect of operating profit on audit report lag. If viem simultaneously the whole starting from the size of the company, opinion and operating profit have an impact on audit report lag Keywords: Audit Opinion, Audit Report Lag, Company Size, and Operating Profit.